A case of spindle cell/pleomorphic lipoma on inferior border of the mandible. Issue 1 (January 2020) - Munakata, Kanako; Asoda, Seiji; Usuda, Shin; Miyashita, Hidetaka; Soma, Tomoya; Hasegawa, Toshihiro; Ogawa, Chiharu; Ohyama, Sadao; Yamauchi, Tomohiro; Kawaida, Miho; Kameyama, Kaori; Nakagawa, Taneaki; et al.
Abstract: Spindle cell lipomas and pleomorphic lipomas are uncommon and distinct variants of benign lipomas. Although spindle cell lipomas and pleomorphic lipomas were originally considered different entities, the recent WHO classification defines them as spindle cell/pleomorphic lipoma (SCL/PL). This is because of their similar clinical features and the existence of intermediate histopathological features between them. A 77-year-old male presented to our clinic with a painless swelling on the left inferior border of the mandible. Computed tomography revealed a clearly defined mass in the subcutaneous lesion. With a histopathological diagnosis of myxolipoma, demonstrated by biopsy, excisional surgery was performed under general anesthesia. The histopathology revealed SCL/PL with the presence of spindle cells and mature adipocytes. No tumor recurrence had been noted at two year after surgery.